Trends in Pharmacological Treatment of Patients With New Onset Type 2 Diabetes: Usage Patterns in an Evolving Guideline Landscape - William Hou; Katherine R. Tuttle; Weining Shen; Andrew Reikes; Jonathan H. Watanabe (Journal of Diabetes)
ABSTRACT Aims In patients with new onset type 2 diabetes, this study aimed to analyze glucose‐lowering medication use patterns between 2014 and 2022. Materials and Methods This retrospective study included adults with incident type 2 diabetes in the University of California Health System between 2014 and 2022. We determined medications used within 1 year of diagnosis and evaluated statistical evidence of use pattern changes via Mann–Kendall trend tests. Four categories of high‐risk patients requiring cardio‐kidney‐metabolic protection were also evaluated in stratified analyses based on 2024 ADA guidelines. Results Of 40 150 patients with incident type 2 diabetes, 38.5% initiated glucose‐lowering medication within 1 year. Metformin remained the most used medication from 2014 to 2022. From 2014 to 2022, usage of GLP‐1 receptor agonists and SGLT‐2 inhibitors increased exponentially. GLP‐1 receptor agonist use increased from below 2.5%–21%. While SGLT‐2 inhibitor use increased from less than 2.5%–14%. This growth coincided with a decline in sulfonylurea usage. Among high‐risk, insulin was most prevalent in those with heart failure or chronic kidney disease. However, usage of insulin declined overall in all groups. Utilization of SGLT‐2 inhibitors was particularly high in patients with prior heart failure. Conclusions In adults with new onset type 2 diabetes, GLP‐1 receptor agonist and SGLT‐2 inhibitor utilization has markedly increased, coordinating with evolving guidelines that emphasize cardiovascular and chronic kidney disease management. However, overall adoption rates of these medications remain low based on indicated populations. Sulfonylurea use declined while metformin remains the most frequently initiated treatment.